Exposure to heavy metals and trace elements among pregnant women with twins: levels and association with twin growth discordance - Chen, Lu; Zhao, Wei; Zhao, Li; Liang, Qiongxin; Tang, Jun; Zhou, Weixiao; Zhang, Yanhua; Wen, Hong (Frontiers in Public Health, 2024)
Background Twin growth discordance is one of the leading causes of perinatal mortality in twin pregnancies. Whether prenatal exposure to heavy metals and trace elements is associated with twin growth discordance has not been studied yet. Objective To evaluate the prenatal level of heavy metals and trace elements in twin pregnancy and its relationship with twin growth discordance. Methods This study involving 60 twin pairs and their mothers was conducted in Zhejiang Province, China, in 2020–2021. The concentration of heavy metals and trace elements in maternal blood, umbilical cord, and placenta were collected at delivery and measured by inductively coupled plasma tandem mass spectrometer. The association of prenatal level with twin growth discordance was evaluated using conditional logistic regression. Results High levels of heavy metal elements (thallium in maternal blood and umbilical cord blood of larger twins, vanadium in the placenta of larger twins) and trace elements (iodine in the placenta of larger twins) during pregnancy, as well as low levels of heavy metal elements (strontium in the umbilical cord blood of larger twins, strontium and chromium in the umbilical cord blood of smaller twins, strontium in the placenta of larger twins, molybdenum and lead in the placenta of smaller twins and difference of molybdenum in the placenta of twins), are associated with intertwin birthweight discordance. Univariate regression analyses showed a significant effect of gestational age at delivery and eleven trace element data on intertwin birthweight discordance. Multivariable logistic regression analysis with transformed variables as dichotomous risk factors combined with baseline demographic characteristics showed Tl in maternal blood as an independent risk factor. The model constructed by combining Tl in maternal blood (OR = 54.833, 95% CI, 3.839–83.156) with the gestational week (OR = 0.618, 95% CI, 0.463–0.824) had good predictive power for intertwin birthweight discordance (AUC = 0.871). The sensitivity analysis results indicate that the effect of maternal blood thallium on intertwin birthweight discordance is stable and reliable. Conclusion To our knowledge, ours is the first case–control study to investigate the association between elevated maternal thallium levels before delivery and twin growth discordance.